منهج الإمام ابن حزم وابن تيمية في عقيدة الروح القدس ومفهوم النصارى عنهIbn Hazm and Ibn Taymiyyah Clarification of the Holy Spirit and its Interpretation in the Christian Belief (Al-Qamar, 2021)
The writer of this article stated the methodology of Imam Ibn Hazm and Imam Ibn Taymiyyah in their clarification of “The Holy Spirit” The concept of Holy Spirit in the Christian doctrine is one of the integral part that cannot be denied as a result of its great impact in the major part of Trinity that determines the Christian basic belief. "The Father the Son and the Holy Spirit” Both Imam Ibn Hazm and Ibn Taymiyyah analyzed the understanding of this concept and its different interpretation and usages in accordance to references from the Quran and Bible. Both Imams stated the references from Tawrah, the Bible and the Holy Qur’an they declared that, The Holy spirit was used for the other Prophets before Prophet ‘Isa bn Maryam (A.S) Angel Jubreel (A.S) was referred to as “Ruh’ l Qudus” which was not acknowledged by the Christian faith. Some other Prophets like Prophet Adam, Dawud, Daniel, Zakariyyah, Ibraheem , Musa (AS)…and others were also addressed as Ruh, in different verses of Holy Qur’an as well as Tawrah and Gospel. Therefore, Prophet ‘Isa was not the only Prophet that had the title of Holy Spirit. Both Imams proves their researches with evidences from the Tawrah, The Bible, The Holy Qur’an, and Hadeeth which were supported by the early Christian scholars.The methods and methodology of the two great scholars include the dialogues with some sects such as Al-Jahmiyyah and others. Conclusively, both Muslims and the early Christian fathers negates the concept of Holy Spirit when it’s single out for Prophet ‘Isa (A.S).